A Simple Method of Analyzing the Phase Transition Behavior of a Na-Sn Battery Using Energy-Dispersive X-Ray Spectroscopy - Byeon, Young-Woon; Choi, Yong-Seok; Seo, Jong-Hyun; Hur, Ka-Hyun; Ahn, Jae-Pyoung; Lee, Jae-Chul (KOREAN INST METALS MATERIALS, 2015)
Anode materials of the Na-Sn battery experience a series of phase transitions during charging and discharging. These phase transitions in many cases are accompanied by a large volume change in the electrode materials, which leads to pulverization, a major source of reducing the battery capacity. In contrast to the rich literature on the phase transition behaviors of the Li-Si battery, those of the Na-Sn battery are much less understood due to experimental difficulties in determining the chemical composition of the phases. In this study, we demonstrate a simple method of analyzing the composition of the reaction compounds of the Na-Sn battery electrodes using energy dispersive X-ray spectroscopy.
Keywords: SODIUM; INSERTION; ANODES